Transitional Care and Adherence of Adolescents and Young Adults After Kidney Transplantation in Germany and Austria: A Binational Observatory Census Within the TRANSNephro Trial. Issue 48 (December 2015) - Kreuzer, Martin; Prüfe, Jenny; Oldhafer, Martina; Bethe, Dirk; Dierks, Marie-Luise; Müther, Silvia; Thumfart, Julia; Hoppe, Bernd; Büscher, Anja; Rascher, Wolfgang; Hansen, Matthias; Pohl, Martin; et al.
Abstract : Abstract: Transition from child to adult-oriented care is widely regarded a challenging period for young people with kidney transplants and is associated with a high risk of graft failure. We analyzed the existing transition structures in Germany and Austria using a questionnaire and retrospective data of 119 patients transferred in 2011 to 2012. Most centers (73%) confirmed agreements on the transition procedure. Patients' age at transfer was subject to regulation in 73% (18 years). Median age at transition was 18.3 years (16.5–36.7). Median serum creatinine increased from 123 to 132 μmol/L over the 12 month observation period before transfer ( P = 0.002). A total of 25/119 patients showed increased creatinine ≥20% just before transfer. Biopsy proven rejection was found in 10/119 patients. Three patients lost their graft due to chronic graft nephropathy. Mean coefficient of variation (CoV%) of immunosuppression levels was 0.20 ± 0.1. Increased creatinine levels ≥20% just before transfer were less frequently seen in patients with CoV < 0.20 ( P = 0.007). The majority of pediatric nephrology centers have internal agreements on transitional care. More than half of the patients had CoV of immunosuppression trough levels consistent with good adherence. Although, 20% of the patients showed increase in serum creatinine close to transfer.